Molecular Systematics of Threatened Seed Plant Species Endemic in the Caribbean Islands - Oleas, Nora (2013)
A review of available Caribbean Island red-lists species (CR and EN categories based on the IUCN guidelines from 2001, and E category established according to the IUCN guidelines from 1980) is presented. A database of over 1,300 endemic species that are either Critically Endangered or Endangered sensu IUCN was created. There are molecular systematic studies available for 112 of them. Six of these species (in six genera) are the only members of early divergent lineages that are sister to groups composed of a large number of clades. Seven of the species (in seven genera) belong to clades that have a small number of taxa but are sister to species/genus-rich clades. Ten of the species (in six genera) are sister to taxa restricted to South America or nested in clades endemic to this region. Fifty-seven of the species (in 35 genera) are sister to Caribbean Island endemic species. Erigeron belliastroides, an Endangered (EN) Cuban endemic, is sister to the Galapagos genus Darwiniothamnus. The phylogenetic placement of four of the threatened species resulted in changes in their taxonomic placement; they belong to polyphyletic or paraphyletic genera. © 2013 The New York Botanical Garden.